Development of Fluid Catalytic Cracking Distributed Simulator Based on IEC 61499 - Wildan Fatkhurrohman; Awang Noor Indra Wardana; Ester Wijayanti (CHEMICA: Jurnal Teknik Kimia, 2020)
Fluid Catalytic Cracking (FCC) is one of the most important process units in oil refining. Operator skill is one of the determining factors for operational success. The operator cannot train his skills at the plant because it will endanger the ongoing process. Operators' skills can be trained through simulation media. This study developed an FCC model IV process simulator to meet these needs. The application of the IEC 61499 standard uses to create simulation models based on IEC 61499 runtime environments (FORTE). Model validation based on reference simulations. The average percentage of error steady under normal operating conditions is 1.63%. Mean Absolute Percentage Error (MAPE) values for changes in the coking factor, atmospheric temperature and feed temperature are 4.40%, 7.26%, and 6.05%, respectively. Modeling of FCC products on 6 components (gas oil, diesel oil, gasoline, light gas, liquid petroleum gas, and coke) was added as a simulation result. Percent of gas oil conversion between simulation results and plant data has an error of 0.12%. The total fraction value of the components of the simulation results is 1.00 for each operating condition. The simulator interface in the form of a human-machine interface (HMI) was developed using Node-RED. Data communication between FCC simulation models on FORTE and HMI on Node-RED uses the Message Queuing Telemetry Transport (MQTT) communication protocol. Implementation of the IEC 61499 standard allows the simulation model to be distributed across several resources. The distribution of resources is done by simulating the FCC process to be run on several FORTE. The FCC simulation model distributed at 2, 4, and 7 resources can reduce memory usage compared to the 1 centralized resource model by 18.0%, 36.0%, and 48.8%.